The fast test for HIV in maternities - Araújo, Carla Luzia F. (2009)
Introduction: in face of the growth of the epidemic of aids among women, the necessity to deepen studies and research to identify to the impact of the actions of prevention of the vertical transmission of the HIV and the vision of the professionals of health of this context. Objectives: to verify if the fast test anti-HIV in the maternities of the city of Rio de Janeiro is being carried on; to describe as the offering of fast test occurs anti-HIV for parturient/pregnant in the maternities, in the vision of health professionals and to analyze the limits and possibilities of the counseling daily pay and after-test front to the fast test anti-HIV in maternities. Methods: qualitative boardingwas used, considering the concepts of completeness of the assistance at the moment of the counseling daily pay and after-test of the fast test for the HIV. The collection of data occurred through half-structuralized, individual, recorded interview in magnetic way and transcribed in the complete one, being organized and detached for categories, using itself the Collective Subject Discourse (DSC). Results: the found emergent categories had been: the practical one of offers of the test anti-HIV for the woman when interned in the maternity; the moment of offers of the test anti-HIV for the woman; the counseling in offers of the fast test for the HIV; the health professional that makes offers and the execution of the fast test anti-HIV; the delivery of the result of the test: between the intervention and the triviality; the factors that had facilitated/had made it difficult to accomplish the fast test for HIV in the maternity; and the vision and suggestions of the professionals of health to improve the accomplishment of the fast test for HIV in the maternity. Conclusion: we conclude that it is possible to offer the fast test for the HIV in the maternities with the accomplishment of counseling daily pay and after-test. However, we conclude that this is not the adequate moment. We still detach for the effective implementation of this practical necessity of qualification of the health professionals, through the qualification and of the availability of necessary resource.